The Effect of Dividend Announcements on Stock Returns for Companies Listed on the Main Board of the Kuala Lumpur Stock Exchange (Malaysian Management Journal, 2002)
Stock market reactions to the announcements of final dividend increases, decreases and no changes are empirically analyzed in an emerging market environment. A standard event study methodology is adopted to examine the price reactions of 120 listed companies surrounding sixty days of the announcement dates. Although prior studies in developed countries postulate that dividend decreases are associated with negative abnormal returns, such a reaction was not found in the Malaysian capital market. The evidence nevertheless shows that dividend increases lead to positive abnormal returns, supporting the Information Content Hypothesis, Jensen :s Free Cash Flow Hypothesis and Agency Cost Theory. As for the no change dividend announcements, no clear pattern of cumulative average abnormal returns could be observed.